Auditor Exits and Firm Performance: Is There a Link?. (March 2023) - Ghosh, Saibal
Employing firm-level data for 2011–2020, we explore the impact of auditor exit on firm performance. Using profitability and growth as outcome variables, the findings suggest that auditor exit leads to a dampening of profit, but growth prospects are not adversely affected. However, firms' stock returns are adversely impacted over the immediate to medium term. This impact differs across ownership, especially when interactive effects are taken on board. Among the reasons, resignations and noncooperation by management are most detrimental to firm behavior. JEL Codes: G 32; M 42